Tracing Biogeochemical Processes Using Sulfur Stable Isotopes: Two Novel Applications - Cousineau, Mélanie L. (Université d'Ottawa / University of Ottawa, 2013)
Abstract Dissimilatory microbial sulfate reduction (MSR) The specific objectives of the study were to provide the first measurements of sulfur isotope fractionation associated with acidophilic sulfate reducing-microorganisms, and to examine whether pH influences sulfur fractionation during MSR. The fractionation associated with the strains investigated was comparable to that of neutrophilic strains with similar metabolisms (4-12‰), but varied with pH. Two fractionation regimes were identified: one regime is consistent with fractionation during exponential growth, while the other – not identified previously - is not linked to active sulfate reduction and may result from internal sulfate accumulation. This would represent the first measurement of sulfur fractionation during sulfate uptake, the first step of MSR. Geological processes at the Cretaceous-Paleogene (KPg) boundary The KPg boundary is associated with one of the largest biological extinctions in the history of our planet. Two major geologic events - the Chicxulub bolide impact with evaporite terrane and the eruption of the Deccan continental flood basalts - coincide with the KPg boundary and have been identified as possible triggers for the extinctions, but their relative timing remains unresolved. The objectives of this study were to identify the contribution of these processes to the sulfur burden in the sedimentary environment of two freshwater KPg sections, and to determine their relative timing. The results demonstrate that the peak of Deccan volcanism post-dates the Chicxulub impact and the associated abrupt KPg mass extinction, thus precluding a direct volcanic causal mechanism, but shedding light on the underlying causes for the delayed recovery of ecosystems in the early Paleogene.
Keywords: sulfur stable isotope; microbial sulfate reduction; isotopic fractionation; Cretaceous-Paleogene extinction; Deccan volcanism; Chicxulub impact